2000
DOI: 10.1021/jf000020k
|View full text |Cite
|
Sign up to set email alerts
|

Potent Fibrinolytic Enzyme from a Mutant of Bacillus subtilis IMR-NK1

Abstract: A mutant of Bacillus subtilis IMR-NK1, which is used for the production of domestic "natto" in Taiwan, produced high fibrinolytic enzyme activity by solid-state fermentation using wheat bran as medium. In addition, a strong fibrinolytic enzyme was purified from the cultivation media. The purified enzyme was almost homogeneous, as examined by SDS-PAGE and capillary electrophoresis. The enzyme had an optimal pH of 7.8, an optimal temperature of 55 degrees C, and a K(m) of 0.15% for fibrin hydrolysis. The molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
71
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(80 citation statements)
references
References 23 publications
7
71
0
Order By: Relevance
“…1, the molecular weight of subtilisin FS33 was estimated to be 30 kDa by SDS-PAGE. This is similar as reported by Takahashi [32] for SMCE (30.0 kDa) of B. pumilus TYO-67, but lower than published for subtilisin E (55.8 kDa), subtilisin IMR-NK1 (31.5 kDa) [33], KK (38 kDa) [34], and KA38 (41 kDa) [25] and higher than for subtilisin NAT (27.7 kDa, formerly designated nattokinase, NK), CK (28.2 kDa), and subtilisin DFE (28.0 kDa). In spite of the strong homology of N-terminal sequences of subtilisin FS33, NK, and subtilisin E, they exhibit different molecular weights and amidolytic activities.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…1, the molecular weight of subtilisin FS33 was estimated to be 30 kDa by SDS-PAGE. This is similar as reported by Takahashi [32] for SMCE (30.0 kDa) of B. pumilus TYO-67, but lower than published for subtilisin E (55.8 kDa), subtilisin IMR-NK1 (31.5 kDa) [33], KK (38 kDa) [34], and KA38 (41 kDa) [25] and higher than for subtilisin NAT (27.7 kDa, formerly designated nattokinase, NK), CK (28.2 kDa), and subtilisin DFE (28.0 kDa). In spite of the strong homology of N-terminal sequences of subtilisin FS33, NK, and subtilisin E, they exhibit different molecular weights and amidolytic activities.…”
Section: Discussionsupporting
confidence: 91%
“…As shown in Table 2, subtilisin FS33 had the highest affinity for N-Succ-Ala-Ala-Pro-Phe-pNA; the studies achieved almost the same level of NK and subtilisin IMR-NK1 [33], their amidolytic activities for the substrate were 14.2 and 16.8 lmol min À1 l À1 , respectively. However, subtilisin FS33, NK, and CK react very differently with D-Val-Leu-Lys-pNA, with amidolytic activities of 0.84, 285.6, and 424 lmol min À1 l À1 , respectively.…”
Section: Discussionmentioning
confidence: 88%
“…Many bacterial Wbrinolytic enzymes were discovered from fermented foods, such as natto [3,[5][6][7], shiokara [8] in Japanese food, Chungkook-Jang [1], Doen-Jang [2], and Jeot-Gal [9] in Korean food, douchi [10] in Chinese food, and Tempeh [11] in Indonesian food. Of them Shiokara (Japan) and Jeot-Gal (Korea) are Wsh-fermented foods, which are used as important additive for improving the taste of other foods as well as being foods themselves [12].…”
Section: Introductionmentioning
confidence: 99%
“…So far, many researchers have focused their efforts on the isolating and screening of microorganisms for enzyme production with high fibrinolytic activity (Chang et al, 2000), as well as on the purifying and characterizing of newly found enzyme (Kim et al, 1996). Evidences suggest that B. subtilis secrete nattokinase.…”
Section: Introductionmentioning
confidence: 99%
“…NK is primarily found from a traditional fermented soybean food named as "Natto" in Japan (Sumi, et al, 1987). It is a subtilisin-like serine protease with molecular weight of 27,000-42,000 Da (Chang, et al, 2000;Fujita, et al, 1993;Kim et al, 1996;Peng, et al, 2003). Besides in vitro tests of fibrinolytic activity, many in vivo studies had been reported.…”
Section: Introductionmentioning
confidence: 99%